BIOECOLOGY OF THE MULBERRY (MORUS, NIGRA L) PLANT USED IN ROAD LANDSCAPING AND PREPARATION OF CUTTINGS IN THEIR VEGETATIVE PROPAGATION - Chorshanbiev Farxod Maxmatmurodovich; Yuldashev Akmal Temirovich (Journals Park Publishing, 2024)
Bioecological characteristics of mulberry (Morus, nigra L) plant species were studied, vegetative reproduction was developed. The use of vegetatively propagated mulberry (Morus, nigra L) species in the landscaping of highways was studied. In the conditions of Uzbekistan, methods of applying mulberry (Morus, nigra L) to scenic greening of highways were developed.
Keywords: Mulberry (Morus, nigra L), decorativeness, resistance to diseases and pests, drought resistance, bioecological properties, vegetative reproduction, highways, landscape landscaping, methods of implementation in Uzbekistan.